3D printed micro/nanofluidic preconcentrator for charged sample based on ion concentration polarization. (29th March 2017) - Pi, Hailong; Tong, Jianhua; Bian, Chao; Xia, Shanhong
Abstract: In this paper, we introduce a novel and simple method to fabricate a preconcentrator based on the ion concentration polarization phenomenon (ICP). Using a three-dimensional printed layer, the microchannels could be easily integrated with an ion exchange membrane which plays the role of the nanoporous junction needed for ICP. To demonstrate the preconcentration ability of the devices, we conducted experiments with negatively charged fluorescein sodium and positively charged rhodamine 6G. As a result, the negatively charged sample could be preconcentrated more than 18 fold by using a cation exchange membrane. The positively charged sample could be preconcentrated more than 40 fold by using an anion exchange membrane. This preconcentrator with a simple fabrication process could be implemented in various microfluidic systems for biochemical assays.